PENGARUH TAKARAN ABU SABUT KELAPA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SEMANGKA (Citrullus vulgaris Schard.) KULTIVAR MAHESA - Umi Trisnaningsih; A Harijanto S; Bambang Bambang (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2014)
The effect of the coconut husk ash dosage on growth and yield of watermelon (Citrullus vulgaris Schard) cv Mahesa.. The research was conducted in the Seda Village, Mundu District Cirebon Regency of the West Java, from April to Juni 2013. This study aimed to determine: (1) the influence of coconut husk ash dosage on growth and yield of watermelon, and (2) doses of coconut husk ash that gives the best growth and yield of watermelon. The method used in this study is an experimental method with a randomized block design (RBD), which consists of one treatmeant factors. The factors coconut husk ash dosage with nine teratmeant were repeated there times. Treatmeant factors are: A = no ash coconut husk ash, coconut husk ash dusk, B = 100 g coconut husk ash dusk / plot, C = 200 kg / plot, D = 300 g / plot, E = 400 g / plot, F = 500 g / plot, G = 600 g / plot, H = 700 g / plot, I = 800 g / plot. The result showed that: no significantly effect of coconut husk ash dosage to the growth and yield of water melon.